Model based precision structural measurements on barely resolved objects - Baddeley, David; Weiland, Y.; Batram, C.; Birk, U.; Cremer, Christoph (Journal of microscopy, 2010)
A model based method for the accurate quantification of the 3D structure of fluorescently labelled cellular objects similar in size to the optical resolution limit is presented. This method is applied to both simulated confocal images of chromatin structures and to real confocal data obtained on a Fluorescence in situ Hybridization (FISH) labelled gene domain. The model assumes that the object is composed of a small number of discrete points which are convolved with the microscope point spread function to give the image. Fitting this model to image data results in a method to assess object structure which is accurate, shows a low bias, and does not require user intervention or the potentially subjective setting of a threshold.